PEMBIASAAN ZIKIR PAGI DALAM PEMBENTUKAN KARAKTER DISIPLIN SISWA MI MAâ€™ARIF NU SUNAN DRAJAT LAMONGAN - Ahmad, Victor Imaduddin; Lutfayanti, Lutfayanti (Akademika, 2018)
A thesis titled â€œpembiasaan all morning develop the character of discipline students mi maâ€™arif nu sunan drajat lamonganâ€Â  it was an research result qualitative aims to answer the question of how pembiasaan all morning in mi maâ€™arif nu sunan drajat lamongan, what are the ones supporting this morning pembiasaan and inhibitors, have all morning pembiasaan discipline students will be able to form the character or not. Approach research used is qualitative descriptive with the kind of research case study on an object. The data collection was done by interviews informants, observation, and documentation. And technical analysis data using descriptive analysis. The results of research obtained is the first pembiasaan remembrance morning very controlled good and tersosialisasi very neat which began at 06.45 wib and ended in at 07.00 wib. Second, by factors in support remembrance morning, regulation clear, homeroom / teacher-chaperon, supervision/controling strict, a guidebook, the leading sector is in control remembrance morning, and the punishment of school, support from of parents/family students, the community, and from friends. Factors barrier of a child who late, difficulty children in reading letters arab, and environmental factors. Third, tutors remembrance morning accompanying read prayer remembrance morning and the supervision of parents families.